Principles of water treatment - Crittenden, John C. 1949-; Howe, Kerry J.; Hand, David W.; Tchobanoglous, George; Trussell, R. Rhodes (John Wiley & Sons, Inc., 2012)
"An abridgement of the reference work Water Treatment, 3rd Edition by the same team of authors, this Student Edition maintains the same quality writing, illustrations, and worked examples as the larger book, but in a more manageable and inexpensive format. All topics are discussed from the ground up, from the basic fundamentals of water chemistry, to filtration, to the design of treatment trains. Designed specifically for civil or environmental engineering students, this edition includes end-of-chapter review questions, chapter summaries, a new glossary, and a solutions manual available online"--